‘Let us enjoy the fruits of our own labour, we have our own solutions’ Creative co-design methods and narratives of Māori whānau with chronic pain - Cheryl Davies; Hemakumar Devan; Kokiri Whānau; Lisa Te Morenga (Kōtuitui)
Chronic or persistent pain disproportionately affects Māori and their whānau (family and significant others). Our previous engagement with Māori living with persistent pain has identified significant barriers for Māori to accessing primary, secondary, and tertiary services. This paper describes the insights obtained from Māori living with persistent pain by using a creative art-based data collection method as part of a co-design process to understand how they would like to be supported in their pain management journey. We used brainstorming discussion sessions and a creative art session to encourage divergent thinking and to stimulate innovative ideas for better pain management support for Māori. The creations showed a deep connection to taiao (nature) and the support of whānau as sources of strength. Connecting with other whānau living with pain in a safe space (i.e. community setting or a marae (community meeting place)) was an aspiration. Existing mainstream services were viewed as deficit-focused with an overwhelming support for Māori-led solutions delivered kanohi-ki-te-kanohi (face-to-face). Creative activities can be used as a culturally appropriate research method for both generating rich insights into the lived experiences of Māori living with persistent pain and how to deliver culturally responsive pain services.